The system for monitoring and express analysis of main equipment of transformer substation 35/6 (10) kv - Galyautdinova, А.Р.; Ivshin, И.В.; Vladimirov, О.В.; Nizamiev, М.Ф. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
There is carried out an analysis and selection of equipment necessary for monitoring and express analysis of the technical condition of a 35/6 (10) kV transformer substation. The authors propose diagnostic parameters for determining the technical condition of equipment and an algorithm for determining the coefficient of express analysis of a transformer substation, which ensures the process of remote monitoring, monitoring the state of operating equipment and predicting changes in the technical condition. The system for monitoring and express analysis of the technical condition of the equipment under development allows online monitoring of changes in the monitored parameters, keeping the equipment in serviceable condition. This monitoring system will make it possible to detect defects at an early stage, to operate the substation's energy equipment more efficiently, and to assess the technical condition of the entire substation in a comprehensive way. The above solutions make it possible to switch to organizing repairs of the substation's main equipment according to the actual state, as well as to increase the reliability and quality of electricity transmission to consumers.